The Neotropical chloropine genus Ischnochlorops Paganelli 2002 (Diptera: Chloropidae), with the description of a new species - Raile, Riccardi Paula; de Souza, Amorim Dalton (Zootaxa, 2013)
A new species is described for the Neotropical genus Ischnochlorops Paganelli (Diptera: Chloropidae), so far known only from the type-species, I. trilineatus Paganelli. The type-species is redescribed based on an additional male from the State of Paraná. A new species, I. lefevrei sp. nov., from Campos do Jordão, State of São Paulo, Brazil, is described. An emended diagnosis is proposed for Ischnochlorops and a key to the species is provided. Photographs of the habitus, head, and wing of both species are provided, as well as drawings of the male terminalia.